Minimization of risks associated with changing the business behavior of IT enterprises - Kompanets, N. I. (Global Prosperity, 2024)
It has been demonstrated that the risk management model associated with changes in the business behavior of IT enterprises due to war takes on a variable, scenario-based nature, which is formed for each enterprise depending on three key variables: response to war, success in operating under martial law, and readiness for post-war changes. The key features of IT enterprises’ risk management are detailed, emphasizing its importance for achieving organizational goals in wartime conditions. The interrelations between risk management and business behavior of the enterprise are specified, taking into account key strategic decisions, tactics, and operational decisions in the organization. The paradox of security and enterprise development, arising against the backdrop of managing conflicting goals of achieving security while simultaneously fostering innovative and risky development in wartime, is characterized. Internal and external security factors of the enterprise are classified, and a refined classification of risks and threats manifested in the operation of IT enterprises is provided. A resolution to the security-development paradox is proposed, considering the theoretical peculiarities and practice of managing IT enterprises, features of risk management, risks, and threats in wartime, and in the context of post-war recovery prospects through the implementation of scenario-based planning for the transformation of business behavior. Considering previous results from the analysis of the peculiarities of managing the business behavior of IT enterprises under martial law, pessimistic, realistic, and optimistic scenarios are described. The main risks associated with changes in the business behavior of IT sector enterprises in Ukraine under different scenarios are detailed. To minimize risks associated with changes in the business behavior of IT enterprises during and post-war, a multi-level system of measures for different levels of enterprise management has been developed, based on the principles of risk management but also considering the prospects of post-war economic recovery and the necessity for future enterprise development to succeed in competitive battles on national and international markets. A model calculation of the balance of costs for security and development depending on the scenarios of business behavior development is substantiated, and detailed recommendations for effective balancing are developed. To strengthen the substantiated recommendations, key managerial competencies necessary for implementing the recommendations are briefly described.